2021
DOI: 10.1289/ehp7813
|View full text |Cite
|
Sign up to set email alerts
|

Sources and Risk Factors for Nitrate and Microbial Contamination of Private Household Wells in the Fractured Dolomite Aquifer of Northeastern Wisconsin

Abstract: BACKGROUND: Groundwater quality in the Silurian dolomite aquifer in northeastern Wisconsin, USA, has become contentious as dairy farms and exurban development expand. OBJECTIVES: We investigated private household wells in the region, determining the extent, sources, and risk factors of nitrate and microbial contamination. METHODS: Total coliforms, Escherichia coli, and nitrate were evaluated by synoptic sampling during groundwater recharge and no-recharge periods. Additional seasonal sampling measured genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(69 citation statements)
references
References 82 publications
2
67
0
Order By: Relevance
“…In particular, deeper depths to bedrock produce longer transport times and more opportunity for attenuation of microbial contaminants (Erb and Steiglitz 2007;Rasmuson et al 2020). Exacerbating this problem, the county's rural landscape is home to potential fecal sources in the form of thousands of private septic systems and tens of thousands of cattle (Borchardt et al 2021). Septic systems are spread ubiquitously throughout the county (Figure 1), and though each is a relatively small source on its own, all are typically located in close proximity to one or more private wells and thus represent a constant hazard of drinking water contamination.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In particular, deeper depths to bedrock produce longer transport times and more opportunity for attenuation of microbial contaminants (Erb and Steiglitz 2007;Rasmuson et al 2020). Exacerbating this problem, the county's rural landscape is home to potential fecal sources in the form of thousands of private septic systems and tens of thousands of cattle (Borchardt et al 2021). Septic systems are spread ubiquitously throughout the county (Figure 1), and though each is a relatively small source on its own, all are typically located in close proximity to one or more private wells and thus represent a constant hazard of drinking water contamination.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its inherent vulnerability and the combination of human and agricultural influences, Kewaunee County's groundwater is in fact regularly contaminated by several different pollutants. Most recently, Borchardt et al (2021) estimated contamination rates of private wells in the county based on the presence of indicator bacteria and/or nitrate and as a function of depth-to-bedrock, which varies from <1 to >45 m across the county (Clayton 2013). More specifically, Borchardt et al (2021) found that 39%-43% of wells constructed in depth-to-bedrock of ≤6:1 m (i.e., ≤20 ft) were contaminated with total coliforms and/or NO 3 − N > 10 mg=L.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations